(untitled) (Applied Biological Research, 2014)
Fifty seven genotypes of gladiolus were assessed for their efficiency with respect to yield and its contributing traits at PAU Ludhiana (Punjab). The higher PCV and GCV estimates were observed for the number of cormels plant-1, weight corm-1and polar diameter of corm. High heritability with high genetic advance was registered for weight corm-1, spike length, number of cormels plant-1, days taken to heading and days taken to open 1st floret. The correlation studies revealed strong positive association of the number of florets spike-1 with the number of leaves, flower duration, spike length, spike diameter, weight corm-1, polar diameter of corm and number of cormels plant-1at both phenotypic and genotypic level. The path analysis indicated that spike length followed by polar diameter of corm and flower duration had highest magnitude of positive direct effect on the number of florets spike-1at phenotypic level, while polar diameter of corm followed by spike length and flower duration had highest direct effect on the number of florets spike-1at genotypic level.